2016
DOI: 10.1080/15592324.2016.1149668
|View full text |Cite
|
Sign up to set email alerts
|

Trait evolution in the slipper orchidPaphiopedilum(Orchidaceae) in China

Abstract: The well-known orchid genus Paphiopedilum has attracted much attention from biologists because of its diverse floral traits. Although these traits have been thoroughly described, little is known about their evolutionary trajectory. In this study, we explored their evolutionary patterns and trajectory through phylogenetic analyses and close observations, and 10 characters in 21 Chinese species mapped onto an existing phylogenetic tree. Lip shape, staminode shape, petal shape, and petal width are relatively cong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 25 publications
(35 reference statements)
0
10
0
3
Order By: Relevance
“…Although orchid flowers are bilaterally symmetric, the inferior ovary or pedicel usually rotates 180° so that the labellum goes on the lower part of the flower to form a platform for pollinators. In Paphiopedilum , the shape of the lip staminode and petal, as well as the width of the petal, are phylogenetically conserved, while flower color is significantly convergent among species (Zhang et al., 2016). The seeds are numerous and extremely small (Arditti, 1992), and exhibit various anatomies (Fig.…”
Section: Important Biological Characteristics Of Orchidsmentioning
confidence: 99%
“…Although orchid flowers are bilaterally symmetric, the inferior ovary or pedicel usually rotates 180° so that the labellum goes on the lower part of the flower to form a platform for pollinators. In Paphiopedilum , the shape of the lip staminode and petal, as well as the width of the petal, are phylogenetically conserved, while flower color is significantly convergent among species (Zhang et al., 2016). The seeds are numerous and extremely small (Arditti, 1992), and exhibit various anatomies (Fig.…”
Section: Important Biological Characteristics Of Orchidsmentioning
confidence: 99%
“…More recently, Zhang & al. () found that the column had similar value in resolving infrageneric relationships in Paphiopedilum . Future studies of the relationship between rostellum morphological diversity and reproductive biology will greatly improve our knowledge of the evolution of the diverse angraecoid lineage.…”
Section: Discussionmentioning
confidence: 93%
“…For example, the structure of the rostellum has been considered a key feature differentiating Margelliantha from Rhipidoglossum (Cribb, 1979). More recently, Zhang & al. (2016) found that the column had similar value in resolving infrageneric relationships in Paphiopedilum.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Otro género de orquídeas de importancia comercial y ornamental es el conocido como zapatilla de dama (Paphiopedilum spp. ), éste comprende alrededor de 96 especies, principalmente con hábito terrestre, nativas de regiones tropicales y subtropicales del sureste de Asia (Wang et al, 2017a), cuyas flores hermosas y llamativas contribuyen significativamente a la industria de la floricultura; sin embargo, su popularidad como plantas ornamentales ha llevado a la sobre recolección de especies silvestres con fines comerciales, lo que ha provocado que algunas especies se encuentran en peligro de extinción y hayan sido puesta en el CITES (Convención sobre el Comercio Internacional de Especies Amenazadas de Fauna y Flora Silvestres) (Zhang et al, 2016).…”
Section: Introductionunclassified